IMPACT OF HERD SIZE ON THE PRODUCTIVE EFFICIENCY OF SHEEP BREEDING PROJECTS AT THE KOKJALI REGION IN NINEVEH GOVERNORATE FOR THE PRODUCTION SEASON 2018 - & et al., Abd (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research was aimed study of the impact of at checking the extent of impact of the herd size on the levels of economic efficiency and its components, to indicate the extent of which optimality is realized in the exploitation of sheep breeding fattening inputs and for a sample of 75 farms in the Kokjali region in Nineveh Governorate and for the productive season 2018, spring batch. To achieve the research goal, the sample was divided into three categories according to the numbers of animals in the farms. To measure the economic efficiency and optimality in using the inputs, the DEA data envelopment analysis and the statistical program DEAP were used, and it was found from the results of the analysis that the research sample projects achieved high levels of technical efficiency averaging 0.962, 0.981, and 0.99 for the three categories respectively as a result of breeders having experience and skill in managing the resources used in breeding, whereas the levels of allocative and economic efficiencies were variable in the three categories; the three large volumes achieved the highest levels and averaged 0.852 and 0.843 for the allocative and the economic efficiencies respectively. The results showed that there is an increase in the rates of inputs use of fodder, duration of fattening and labor in the research sample, and a decrease in the use of primary weight inputs and the veterinary services. The third category, which is the largest, achieved the lowest increase and decrease rates compared to other categories, Thus, we recommend the breeders in the research sample projects to take advantage of economies of scale and to exploit barns capacity in proportion to the numbers of animals, and the decision-makers not to follow the open market policy and to put restrictions on smuggling and entry of animals to the country, as well as the necessity of supporting the prices for veterinary services and feed.